Few-layer graphene coated current collectors for safe and powerful lithium ion batteries - Kim, So Yeun; Il Song, Young; Wee, Jae-Hyung; Kim, Chang Hyo; Ahn, Byung Wook; Lee, Jung Woo; Shu, Su Jeong; Terrones, Mauricio; Kim, Yoong Ahm; Yang, Cheol-Min (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
In the fabrication of safe, but powerful lithium ion batteries (LIBs), graphene-related materials are being actively examined in order to meet the demand for applications such as electric vehicles and smart grids. However, most of this work has focused on liquid-phase exfoliated graphene and reduced graphene oxide. Herein, we demonstrate a simple, but effective route for significantly improving the electro-chemical performance of currently available LIBs by coupling current collector with catalytically grown large-area graphene. When coating current collectors with large-area three-layered graphene, a reduction in the internal resistance (or effective electron transfer) between the current collector and active materials was observed. The graphene also protected the underlying collector from corrosion, greatly improving the power capability and cyclability of LIBs. The three-layered graphene provided the best electrochemical performance and corrosion resistance because of its high electrical conductivity and mechanical stability during the transfer process. We believe that our approach using interfacial graphene coating can be used with all kinds of electrochemical energy-storage systems, in which high corrosion resistance, electrical conductivity, and flexibility are critical. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: ELECTROCHEMICAL PERFORMANCE; ALUMINUM FOIL; STABILITY; GRAPHITE; CATHODES; BINDERS; ISSUES; FILMS; OXIDE